Penerapan Gamifikasi dalam Pembelajaran Kalkulus untuk Meningkatkan Motivasi dan Pemahaman Mahasiswa - Gerfasius Take Piran; Claudia Betrucy Bada; Yohanes B. M. Darkel (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore the application of gamification in calculus learning as an effort to improve students' motivation and understanding. Gamification, which integrates game elements in a non-game context, is expected to create a more engaging and interactive learning experience. The method used in this study was an experiment involving two groups of students, namely a control group using conventional learning methods and an experimental group implementing gamification in the teaching and learning process. The results showed that the application of gamification significantly increased students' learning motivation, which was reflected in increased active participation and enthusiasm in attending lectures. In addition, the analysis of the understanding of calculus concepts also showed positive results, where the experimental group showed higher scores in the evaluation of material understanding compared to the control group. This study concludes that gamification can be an effective strategy in calculus learning, not only to increase motivation but also to deepen students' understanding of the material being taught.